Erratum: Analysis of isotope effects in NMR one-bond indirect nuclear spin-spin coupling constants in terms of localized molecular orbitals - Provasi, Patricio Federico (2010)
The numerical values given for the reduced coupling constants, KX–H (in 1018 J 1 T2 ), and for the changes in the reduced coupling constants, DKX–H (in 1018 J 1 T2 ), in Tables 2 to 7 and Figures 1 to 4 have to be multiplied by the constant factor p. These changes have no influence on the discussion or conclusions of the paper as all values are equally affected.